2019
DOI: 10.18261/issn.2387-5984-2019-03-08
|View full text |Cite
|
Sign up to set email alerts
|

Using GPS Technologies with People with Dementia

Abstract: In Norway and other Nordic countries, there is a policy emphasis on using welfare technologies to support people to live at home. For example, Global Positioning Systems (GPS) or 'location technologies' are used to support people with dementia and their next of kin with wayfinding. However, the research evidence has not been synthesised, and so the opportunities and challenges presented when using GPS technologies are not clear. This synthesising review examined all available empirical evidence on the use of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…RenderX [10][11][12]. The previous reviews provided a broader picture of state-of-the-art research on GPS tracker use in older adult care [10] and for managing wandering behavior among persons with dementia [11].…”
Section: Xsl • Fomentioning
confidence: 99%
See 3 more Smart Citations
“…RenderX [10][11][12]. The previous reviews provided a broader picture of state-of-the-art research on GPS tracker use in older adult care [10] and for managing wandering behavior among persons with dementia [11].…”
Section: Xsl • Fomentioning
confidence: 99%
“…Interestingly, no overlap in the included studies was identified between the review by Neubauer et al [11] and this review. However, this review had a small overlap of four studies with a synthesizing review by Bartlett et al [12], which included empirical studies of persons with dementia or their family CGs or both using GPS. A total of 23 studies published in the period 2007-2016 were included, and data were synthesized across three identified themes: using GPS to prevent harm and promote well-being; taking control; and value of GPS data [12].…”
Section: Xsl • Fomentioning
confidence: 99%
See 2 more Smart Citations
“…The different variations that have emerged from the analysis include environmental support and space, settings and infrastructure. In the Nordic countries, the policy emphasises using AT/WT to enable and support older people to stay and live at home [25]. For example, "smart homes" might enable older people with different impairments to participate in the daily living and increasingly use smart technology to support them with the connected technologies integrated into the buildings [26].…”
Section: Discussionmentioning
confidence: 99%